2021
DOI: 10.1002/brb3.2158
|View full text |Cite
|
Sign up to set email alerts
|

Association between neurological outcome and poststroke comorbid mood and anxiety disorders: A real‐life experience

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Introduced by Alexopoulos et al [ 27 ], it proposed that cerebral small vessel disease (CSVD), in particular subcortical microvascular dysfunction and white matter hyperintensities (WMH), microbleeds and lacunes in gray matter, may predispose, precipitate, and perpetuate depressive symptoms in aged people as a consequence of structural damage in the fronto–subcortical circuits [ 23 , 27 , 28 ]. This hypothesis is based on the observation that cerebrovascular risk factors are frequently present in aged individuals with depression, its comorbidity with cerebrovascular lesions, and the frequent development of depression after stroke, affecting between 20% and 30% of all stroke patients [ 29 , 30 , 31 ]. Cerebrovascular burden in midlife predicts depressive symptomatology in later life, suggesting an interrelation between cerebrovascular burden and LLD [ 32 ].…”
Section: The “Vascular Depression Hypothesis”mentioning
confidence: 99%
“…Introduced by Alexopoulos et al [ 27 ], it proposed that cerebral small vessel disease (CSVD), in particular subcortical microvascular dysfunction and white matter hyperintensities (WMH), microbleeds and lacunes in gray matter, may predispose, precipitate, and perpetuate depressive symptoms in aged people as a consequence of structural damage in the fronto–subcortical circuits [ 23 , 27 , 28 ]. This hypothesis is based on the observation that cerebrovascular risk factors are frequently present in aged individuals with depression, its comorbidity with cerebrovascular lesions, and the frequent development of depression after stroke, affecting between 20% and 30% of all stroke patients [ 29 , 30 , 31 ]. Cerebrovascular burden in midlife predicts depressive symptomatology in later life, suggesting an interrelation between cerebrovascular burden and LLD [ 32 ].…”
Section: The “Vascular Depression Hypothesis”mentioning
confidence: 99%
“…Finally, and perhaps most significantly, the findings of this study supported the CSM's (Walker et al, 2009 ) theoretical framework and complemented the significance of perceived recurrence risk and coping mechanisms in individual health outcomes. Stroke is a chronic and dynamic disease (Rabat et al, 2021 ). It is critical that stroke survivors view the chance of recurrence favourably.…”
Section: Discussionmentioning
confidence: 99%
“…PSD, one of the most frequent stroke consequences (Shi et al, 2017 ), may have a negative impact on the course of stroke survivors. PSD has been proven to impair the recovery of motor and cognitive function in several studies, which lowers the quality of life for stroke survivors and raises the risk of recurrence and mortality (Lu et al, 2019 ; Rabat et al, 2021 ). According to Ge et al ( 2014 ), PSD is more common in rural areas due to the subjective characteristics of stroke survivors and objective aspects of the environment (Zemed et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may be due to a common inflammatory and vascular factor underlying stroke, AD, and for example depression 27 . Stroke can also cause or be a trigger for depression 28 . Asthma/COPD was slightly associated with belonging to the Prodromal group.…”
Section: Discussionmentioning
confidence: 99%
“…27 Stroke can also cause or be a trigger for depression. 28 Asthma/COPD was slightly associated with belonging to the Prodromal group. Previous studies have shown that hypoxemia correlates with neuropsychological impairment.…”
Section: Other Characteristics Associated With Belonging To the Prodr...mentioning
confidence: 92%